2021
DOI: 10.1097/jan.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Opioid Use Disorder Patients Receiving Buprenorphine Through a Telehealth Program

Abstract: Background Opioid use disorder (OUD) continues to be a growing and major public health issue in the United States. In an effort to increase OUD treatment access, medication-assisted treatment with buprenorphine via telehealth is emerging as the leading treatment option. Objective This study sought to describe the experiences of adults with OUD receiving medication-assisted treatment buprenorphine in a nurse-practitioner-facilitated telehealth program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Almost all studies were published between 2020 and 2022, with the exception of two published in 2018 and 2019. Most commonly, studies employed a retrospective design ( n = 10) [ 8 , 12 , 22 29 ], a qualitative design ( n = 7) [ 10 , 30 31 , 32 •, 33 – 35 ], or a case study design ( n = 6) [ 36 – 40 , 41 •]. The rest followed a mixed-methods approach ( n = 2) [ 16 , 42 ], a prospective cohort design ( n = 1) [ 43 ], non-randomized control trial ( n = 1) [ 44 ], cross-sectional design ( n = 1) [ 45 ], or a commentary approach narrating experience ( n = 2) [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Almost all studies were published between 2020 and 2022, with the exception of two published in 2018 and 2019. Most commonly, studies employed a retrospective design ( n = 10) [ 8 , 12 , 22 29 ], a qualitative design ( n = 7) [ 10 , 30 31 , 32 •, 33 – 35 ], or a case study design ( n = 6) [ 36 – 40 , 41 •]. The rest followed a mixed-methods approach ( n = 2) [ 16 , 42 ], a prospective cohort design ( n = 1) [ 43 ], non-randomized control trial ( n = 1) [ 44 ], cross-sectional design ( n = 1) [ 45 ], or a commentary approach narrating experience ( n = 2) [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seeing the publication time period, perhaps the most reported non-clinical outcomes related to improving access to care in the context of mobility restrictions, especially among hard to reach and rural populations. For instance, some authors reported improved outreach with vulnerable patients, reduced wait times, and improved access to treatment upon transitioning to tele-MOUD [ 10 , 23 , 25 , 37 , 40 ]. Authors attributed these findings to the ability of tele-MOUD to bypass issues such as childcare, work commitments, transportation challenges, stigma, and increased flexibility in scheduling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on new working practices emerged at the time of this study, so it is difficult to draw conclusions about how different cohorts adjusted. Similar to the participants in the current study, some have argued that telehealth provision has facilitated easier access to services ( Molfenter et al, 2021 ), and others are concerned that particular cohorts have struggled with access to technology and isolation ( Moore et al, 2021 ). Limited data exist from the service users' perspective.…”
Section: Discussionmentioning
confidence: 79%